The Role of Reflexive Support of University Students in the Learning Process - Usheva, Tatyana F. (International Journal of Psychosocial Rehabilitation, 2020)
Modern university education has undergone a change in the 'teacher - student' relationship. Joint research in the world of the new and unknown has made students full-fledged contributors and co-creators in the process of learning. However, although the way of interaction has changed, the role of the teacher in establishing learning environment still remains 'meta-positional'. The topicality of this research lies in the demand of the modern society for a new type of professionals who can face its challenges. The research provides theoretical framework for the problem of university training of students.The article presents results of implementation of reflective approach principles: individualization of learning, establishment of a learning dialog, analysis of pedagogical work from the positions of the teacher, student and meta-position, developing subject-to-subject relations in the course of learning.The main approach to study this problem is reflective approach which helps provide pedagogical support to every student individually.Longitudinal procedures and methods were used to study undergraduate and master's students studying psycho- pedagogical education and aged 17-21 and 22-35 respectively. The analysis of data was performed for 82 students.Our experimental study proves pedagogical relevance, need and feasibility of putting the principles of reflective approach into practice. Psycho-pedagogical study found positive effect of reflexive support on the learning process. As early as at the second stage of the experiment students from experimental group gained and mastered the experience of studying in aggregated or permanent groups and the experience of individual, group and collective reflection. They started analyzing what drove their behavior. Having mentioned external factors along with internal ones, in most cases they found the causes in themselves, their actions and abilities. However, over the two years of study, master’s students did not reach the same level as undergraduates, even though they belonged to an older age group. Based on the analysis of reflective skills of every type, it is possible to observe a certain pattern in their development: personal and communication skills are formed first while intellectual and cooperative ones are built upon them.The results presented in the article can be used by lecturers and researchers who train future pedagogues and tutors as well as related professionals such as teachers and psycho-pedagogues.